Beyond Use Date of Rifampicin Pulverized and Its Influencing Factors - Zaldy Rusli; Septia Andini; Nisa Najwa Rokhmah; Idul Suci Fitriana; Mutiara Apriliana Suvitri (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Inaccurate drug dosage during Tuberculosis (TB) therapy is one of the factors causing TB resistance, especially for drugs that undergo a compounding process, which are often prescribed for children. Inappropriate storage of drugs during therapy can cause a reduction in drug content, which results in changes in drug dosage, therefore drugs should be used within a certain time limit or what is known as the Beyond Use Date (BUD). This study aims to determine the BUD in rifampicin powder preparations from a hospital in the Bogor district. Rifampicin powder preparations are packaged in 3 types of packaging (paper silk, parchment and capsules). Storage wascarried out at 2 temperatures, namely room temperature 25-28 °C and warm temperature 30-35 °C. Rifampicin levels were analyzed using High Performance Liquid Chromatography (HPLC). The results showed that the BUD of paper silk, parchment and capsule packaging at room temperature were 8, 11, and 14 days respectively, while storage at warm temperatures was 11, 10, and 12 days. This study stated that rifampicin powder preparations should be used for 7-13 days. Factors that affect BUD are the moisture content of the preparation, the container (type of packaging) and the storage conditions (temperature).